Role of the Demethylase AlkB Homolog H5 in the Promotion of Dentinogenesis - Tian, Cheng; Chai, Jihua; Liu, Weidong; Zhang, Xinye; Li, Yashu; Zuo, Huanyan; Yuan, Guohua; Zhang, Haojian; Liu, Huan; Chen, Zhi (Frontiers in Physiology, 2022)
Dentinogenesis is a key process in tooth formation and is regulated by a series of pre- and post-transcriptional regulations. N6-methyl-adenosine (m6A), which is the most prevalent internal chemical modification that can be removed by the RNA demethylase AlkB homolog H5 (ALKBH5), has recently been reported to be involved in several biological processes. However, the exact function of ALKBH5-mediated m6A modification in tooth development remains unclear. Here, we showed that Alkbh5 was expressed in pre-odontoblasts, polarizing odontoblasts, and secretory odontoblasts. Alkbh5 overexpression in the mouse dental papilla cell line mDPC6T promoted odontoblastic differentiation. Conditional knockout of Alkbh5 in Dmp1-expressing odontoblasts led to a decrease in number of odontoblasts and increased pre-dentin formation. Mechanistically, RNA sequencing and m6A sequencing of Alkbh5-overexpressing mDPC6T cells revealed that Alkbh5 promoted odontoblast differentiation by prolonging the half-life of Runx2 transcripts in an m6A-dependent manner and by activating the phosphatidylinositol 3-kinase/protein kinase B pathway. Notably, the loss of Alkbh5 expression in odontoblasts impaired tertiary dentin formation in vivo. These results suggested that the RNA demethylase ALKBH5 plays a role in dentinogenesis.